Prevalence, incidence, and the time trends of sleep-disordered breathing among patients with stroke: a systematic review and meta-analysis - Su, Xiaofeng; Liu, Shanshan; Wang, Cong; Cai, Yan; Li, Yijing; Wang, Dongmin; Fan, Zhaofeng; Jiang, Yan (Frontiers in Neurology, 2024)
BackgroundRecent studies have investigated the epidemiological burden of sleep-disordered breathing (SDB) in patients with stroke; however, the results have been inconsistent, and the temporal trends of SDB after stroke remain unclear.ObjectiveTo perform a systematic review and meta-analysis of the prevalence and incidence of post-stroke SDB, evaluate demographic and clinical characteristic predictors of post-stroke SDB, and examine temporal trends in the overall burden of post-stroke SDB.MethodsWe searched PubMed, MEDLINE, Embase, Web of Science, CINAHL, and the Cochrane Library for studies reporting the burden of SDB in stroke patients published between 1 January 2010 and 30 December 2023. Two researchers independently screened the records for eligibility, extracted the data, and assessed the quality of the studies. Data were analyzed using random effects meta-analyses, and sources of heterogeneity were explored using subgroup analyses and meta-regression analyses.ResultsOut of the 8,799 references retrieved, none examined the incidence of SDB after stroke. However, 85 studies from 26 countries examined the prevalence of SDB and were included. The overall prevalence of SDB, mild SDB, and moderate to severe SDB were 60.0% (95% CI, 60.0–70.0%), 30.0% (95% CI, 23.0–37.0%), and 45.0% (95% CI, 33.0–57.0%), respectively. Meta-regression revealed that sex (p < 0.0001) and sample size (p < 0.01) were sources of heterogeneity among the studies. The pooled overall prevalence of SDB remained stable over time.ConclusionSDB is common in patients with stroke, and no reduction in the high prevalence of SDB has been observed over time, suggesting that early screening and prevention of post-stroke SDB still have not received sufficient attention. Moreover, additional studies investigating the incidence of this disease are needed to inform clinical practice.